Muay Thai - Veere, Arnaud van der. (Auckland : Meyer & Meyer Sport, 2012)
The book shows the basic of the challenging sport Muay Thai. Learn the techniques and understand how to apply them. Numerous exercises guarantee a varied and interesting training. Besides the total workout of the body, the sport improves personal awareness, stamina and physical control.
Keywords: Muay Thai; Kickboxing -- Thailand